Teachers’ Perceptions of The Role of The Merdeka Curriculum in Shaping Students’ Character in The Digital Era - Nurmadiyah; Husarida (Lembaga Bale Literasi, 2025)
The rapid development of digital technology has significantly influenced the educational environment, particularly in relation to students’ character formation. The widespread use of digital media exposes students to various challenges, including misinformation, cyberbullying, and the weakening of moral values. In response to these issues, contemporary education is expected to emphasize not only academic achievement but also the development of strong character. In Indonesia, the Merdeka Curriculum was introduced as an educational reform that provides greater flexibility in learning while integrating the Pancasila Student Profile to strengthen character education. This study aims to explore teachers’ perceptions regarding the role of the Merdeka Curriculum in shaping students’ character in the digital era at Madrasah Tsanawiyah Nururrodhiyah, Jambi City. The research employed a descriptive qualitative approach. Data were collected through observations, semi-structured interviews, and documentation involving teachers and school stakeholders. The data were analyzed using data reduction, data presentation, and conclusion drawing, supported by triangulation to ensure credibility. The findings indicate that most teachers have a positive perception of the Merdeka Curriculum. They consider the curriculum to provide flexibility in teaching practices and encourage innovative learning that supports the development of independence, responsibility, critical thinking, and digital literacy. However, several challenges were identified, including limited facilities, differences in teachers’ technological readiness, and difficulties in understanding instructional modules. Overall, the Merdeka Curriculum has a strategic role in strengthening students’ character in the digital era, although continuous institutional support and teacher professional development remain necessary.